cis-Diamminedichloroplatinum(II)-induced cell death through apoptosis in sensitive and resistant human ovarian carcinoma cell lines - Ormerod, M G; O'Neill, C; Robertson, D; Kelland, L R; Harrap, K R (Cancer chemotherapy and pharmacology, 1996)
We have studied the effects of the chemotherapeutic drug cis-diamminedichloroplatinum(II) (cis-platin) on three human ovarian carcinoma cell lines - one sensitive to the drug (CH1), one with acquired resistance (CH1cisR) and one with intrinsic resistance (SKOV-3). Previous work has shown that the 50% inhibitory concentrations (IC50 values) after a 2-h exposure to the drug are: CH1, 2.5 microM; CH1cisR, 7.5 microM; and SKOV-3, 33 microM. Despite the variation in sensitivity, the amount of Pt bound to DNA and the rate of removal of Pt was similar for the three lines. There were significant differences in the rates of formation of DNA cross-links but these were not large enough to account for the high resistance of the SKOV-3 line. We have reported that in the L1210 murine leukaemia cell line there are two mechanisms of cisplatin-induced cell death - one of which involves apoptosis. In this paper, we report on an investigation into whether sensitivity to apoptosis played a role in the resistance of these ovarian lines toward cisplatin. After a 2-h incubation with the drug, cells from the three lines showed evidence of death through apoptosis. The cells detached from the culture dish in a time- and dose-dependent fashion. These cells morphologically were quite distinctive from the attached cells and showed changes in their chromatin structure indicative of apoptosis. Their DNA had not been degraded into oligonucleosomal fragments (200 bp and multiples thereof) but had been cut into larger fragments (30 kilobase pairs, kbp) of a size associated with chromatin domains (chromatin loops). At equitoxic doses of drug, the quantity of cells undergoing apoptosis was similar for the three cell lines. The most prominent effect on cell-cycle kinetics was a slowdown in S-phase transit during which the cells underwent apoptosis. Cells that successfully completed the S phase subsequently suffered a temporary G2 block. We propose that the sensitivity of these cell lines to cisplatin was governed by their ability to handle damage caused by platination of the DNA and that the major mechanism of cisplatin-induced cell death in all three cell lines was the induction of apoptosis.